Optimalisasi Rute Truk dalam Proses Pendistribusian Produk Biskuit dan Snack dengan Algoritma Nearest Neihbour dan Neirest Insertion: Studi Kasus PT Siantar Top Tbk. Medan - Nisha Zahara; Resista Vikaliana (Jurnal Civronlit Unbari, 2023)
PT Siantar Top Tbk. Medan is a company engaged in the business of snacks in the form of biscuits and snacks. The existence of the Covid-19 pandemic has caused paralysis of almost all human activities which have an impact on a lot of work being done remotely or WFH which can trigger one's boredom in doing some work and thinking about consuming snacks. So the demand for snacks also increases. Of course this is a great opportunity for the company to increase revenue. The increase in demand must also be followed by a good and optimal distribution system. This study aims to determine the truck route in the distribution process of biscuit and snack products. This research was completed by using the Nearest Neighbor and Nearest Insertion methods which will then be compared between the company's initial route and the routing results route by considering the vehicle capacity both in terms of distance traveled and shipping costs. Based on the routing results, it is found that the route with the Nearest Neighbor method is the same as the Nearest Insertion method, namely the total distance generated is 3,360.8 km or with a distance savings presentation of 38.88%. These results greatly affect the shipping costs incurred by the company, namely from Rp. 5. 918,997,- to Rp. 3,527,301,-. So it can be concluded that the company's distribution route that was previously used needs to be improved. The repair can use both methods because the result is the same.